Field evaluation of yellow stem borer, Scirpophaga incertulas (Walker) incidence in selected rice genotypes: Field screening for resistance against rice yellow stem borer - Balaji, BN; Vijaykumar, L; Shivanna, B (ORYZA-An International Journal of Rice, 2025)
An evaluation of 26 local landraces and ten popular cultivars for resistance to paddy yellow stem borer (YSB), Scirpophaga incertulas (Walker), was conducted at the College of Agriculture, V.C. Farm, Mandya, during the kharif 2022 and Summer 2023 seasons. The percentage of YSB damage across various genotypes was assessed at 30, 60, and 90 days after transplanting (DAT). Based on the mean percentage of infestation, the genotypes were classified into different resistance categories according to the Standard Evaluation System for Rice (SES) developed by IRRI. Among the 26 local landraces, five genotypes demonstrated resistance with a damage score of 1, nine were moderately resistant with a score of 3, eight genotypes were moderately susceptible with a score of 5, and four genotypes were classified as susceptible with a score of 7 across both seasons, showing varied infestations. Of the popular cultivars evaluated, four genotypes showed resistance, four were moderately resistant, one was moderately susceptible, and one was susceptible during Summer 2023. No genotypes, either local landraces or popular cultivars, displayed high resistance or high susceptibility to YSB.